On Common Ground: Translocal Attachments and Transethnic Affiliations in Agha Shahid Ali’s and Arthur Sze’s Poetry of the American Southwest - Judith Rauscher (European Journal of American Studies)
Combining insights from human geography, critical regionalism, and environmental literary criticism, I argue that the concept of the translocal, rather than the transnational, is useful to describe the complex poetics of place in Agha Shahid Ali’s A Nostalgist’s Map of America (1991) and Arthur Sze’s The Ginkgo Light (2009). Engaging with landscapes of the American Southwest and elsewhere, and in particular with the natural environment, both poets reimagine the region as a site of translocal attachments and as the grounds for transethnic affiliations, especially with local Native American peoples. What emerges from this inclusive and yet open sense of belonging to place is an ethics of being in and with nature that attempts to reckon with the increasing pressures of both globalization and global environmental crisis. Literature, as Ali’s and Sze’s poetry suggest by foregrounding poetic strategies like intertextuality and metaphorical language, plays a central role in the development of such an ecologically suggestive ethics of place in the context of migration and displacement.